Effect of the parasitoid Cephalonomia stephanoderis (Hymenoptera: Bethylidae) on Hypothenemus hampei (Coleoptera: Scolytidae) during and after harvest - ARISTIZÁBAL-A., LUIS F.; BUSTILLO-P., ALEX E.; OROZCO-H., JAIME; CHAVES-C., BERNARDO (Revista Colombiana de Entomología, 1998)
In order to evaluate the effect of the parasitoid C. stephanocleris on the populations of H. hampei during and after the main harvests and crossbeam of coffee and to facilitate the implementation of the parasitoids in the integrated pest management program, the present investigation was made in Colombian variety of coffee, crops located at Experimental Subestaciones: Naranjal in Chinchiná. La Catalina in Pereira and the farm El Porvenir in Armenia and Dinamarca in Calarcá. Four treatments were established according to the time of release: treatment 1(Control, without liberation), treatment 2 (liberation before the harvest), treatment 3 (liberation after the harvest), and treatment 4, a combination of both releases (before and after the harvest). The results demonstrated the presence of C. stephanoderis in all the crops in which it was released. During the first five months, parasitisms between 3 - 28 %, were observed, months in which the levels of infestación of H. hampei remained low and stable with respect to the control. A significant reduction of the infestación levels of H. hampei, of the average number of fruits infested per tree and of the biological states of the pest in the crops in where the parasitoid was released. with respect to the control was observed. Also, coffee was obtained parchment type federation during both harvests. The best behavior of the parasitoid was observed when the combination of both releases was made (before and after harvest). Therefore the releases of C. siephanocleris within an integrated pest management program should be made in the winter harvest periods, that is to say, before and after the main harvest and crosshead. It was observed that the releases of C. stephanorleris plus the opportune harvesángs of mature fruits help to regulate the populations of H. hampei, maintaining levels of infestación lower than 5% during a harvest period.